Summer Thermal Comfort Zoning Studies of Mainland China Based on the Comprehensive Heat Index - Yingfeng Guo; Zhifeng Wu; Zihao Zheng; Xiaojun Huang; Zhongwen Hu (International Journal of Climatology, 2025)
With global warming, a better understanding of the summer thermal environment is crucial. Distinct from land surface temperature, which is the most widely noticed and employed parameter of the summer thermal environment, we constructed the Summer Comprehensive Heat Index using six common heat indices (outdoor apparent temperature, heat index, Humidex, modified discomfort index, net effective temperature, and simplified wet‐bulb global temperature) through principal component analysis, analysing its spatial distribution and temporal trends (2003–2020) at 10 km grid and county scales across mainland China. Employing Automatic Regionalisation with Initial Seed Location, Regionalisation with Dynamically Constrained Agglomerative Clustering and Partitioning, and Spatial Kluster Analysis by Tree Edge Removal regionalisation methods with spatially constrained and classical statistical approaches, a two‐tier geographical division of summer thermal comfort zones was conducted. Results indicate severe thermal stress in Southern China and the Bohai Rim regions, while regions such as the marginal region of the Tibetan Plateau, Inner Mongolia Plateau, and Yungui Plateau offer high thermal comfort, suitable for ‘sunbird’ tourism. Conversely, the Bohai Rim and lower Yangtze regions exhibit extreme heat stress with intensifying warming trends, calling for urgent adaptation. The study highlights regional thermal heterogeneity, providing insights for localised tourism planning and climate resilience strategies.